The Effect of Accounts Receivable Accounting Information System, Internal Control System and Service Quality on Receivables Collectability In BPJS Ketenagakerjaan Bandung Lodaya - Wardani, Intan Kusuma; Syarif, Devyanthi (Journal of Accounting Inaba, 2023)
The research method used is Quantitative with Descriptive and Verification approaches. The type of data source used is primary. With sampling techniques using non-probability sampling with a saturated sampling approach. The results of the statistical description test study show that each respondent's question from the variables of Collectability of Receivables, Accounts Receivable Accounting Information System, Internal Control System, and Service Quality of employees of the Social Security Administration Agency / BPJS Ketenagakerjaan Bandung Lodaya has a good category. The results showed that hypothesis testing obtained the following results: (1) the Accounts Receivable Accounting Information System influences the Collectability of Receivables, (2) The Internal Control System affects the Collectability of Receivables, (3) Service Quality affects the Collectability of Receivables. (4) the Accounting Information System, Internal Control System, and Service Quality significantly affected the Collectability of Receivables